Economic model of regenerative agriculture and factors of agri-food system change - Daniela Trifan; George Toaders; Cătălin-Ioan Enea; Alin-Ionel Ghiorghe; Emanuela Lungu; Elena-Violeta Toader; Leonard Ilie (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The basis of regenerative agriculture is represented by its main element, namely the soil. Ensuring good soil health will lead to many beneficial effects on agricultural ecosystems. Among the main beneficial effects of soil health we can list the management of groundwater resources and irrigation systems at large agro-zootechnical farms, recycling of nutrients from and to the soil surface with the help of green, environmentally friendly fertilizers and agroecosystems, maximizing crop yields, sustainability of crops, soil and productivity per hectare, sustainability of agri-food and livestock farms. The fact that through regenerative agriculture, organic carbon in the soil structure can be exploited in order to maximize agricultural productivity and restore soil structure, regenerative agriculture focuses mainly on restoring soils that have suffered great degradation due to their acidification by using large amounts of pesticides and chemical fertilizer products. This article aims to present the economic principles and methods of regenerative agriculture so that these processes combined into a unitary whole lead to the restoration of soil organic matter naturally, the principles of regenerative agriculture practitioners being that nature can regulate automatically the imbalances identified in nature. The less minimal the interventions on the soil, the less the residues from agriculture (reductions resulting from the activity of fertilization and plant protection) will be minimal, the products used will present a minimum invasiveness, which will lead to the acceleration of the recovery processes. soil, to balance the electrolyte balance of the soil and, implicitly, to develop the root system of plants so as to ensure a sufficient amount of mineral elements in the soil, in order to maximize agricultural production.
Keywords: Q01; Q34; Q57; 330; organic farming; regenerative agriculture; farm profitability; food system; policy makers